Evaluation of Buruli Ulcer Disease Surveillance System in the Ga West Municipality, Ghana, 2011–2015 - Tanko Rufai; Enoch Aninagyei; Samuel Oko Sackey; Ernest Kenu; Edwin Andrew Afari (Journal of Tropical Medicine)
Background. Buruli ulcer (BU) is one of the most neglected tropical diseases caused by Mycobacterium ulcerans. M. ulcerans infection may manifest initially as a pre-ulcerative nodule, a plaque, or oedema which breaks down to form characteristic ulcers with undermined edges. The Ga West Municipality is an endemic area for Buruli ulcer, and we evaluated the BU surveillance system to determine whether the system is meeting its objectives and to assess its attributes. Materials and Methods. We used a checklist based on Centers for Disease Control and Prevention (CDC) updated surveillance evaluation guidelines, 2006. We reviewed records and dataset on Buruli ulcer for the period 2011–2015. The evaluation was carried out at the national, regional, district, and community levels using the Ga West Municipality of the Greater Accra Region as a study site. Interviews with key stakeholders at the various levels were done using an interview guide, and observations were done with a checklist. Data were entered and analyzed using Epi info 7. Results. A total of 594 cases of Buruli ulcer were reported from 2011 to 2015 in Ga West. The number of confirmed cases decreased from 109 in 2011 to 17 in 2015. The system was useful, fairly simple, flexible, representative, and fairly acceptable. The system was sensitive with a PVP of 45.3%. Although the data quality was good with 85% of case report forms completed, there was under-reporting (3.6%), some discrepancies of data at the district, regional, and national levels. The system was moderately stable, and timeliness of reporting was 30.7%. Conclusion. The Buruli ulcer surveillance system is meeting its set objectives, and the data generated are used to reliably describe the epidemiologic situation and evaluate the results for actions and plan future interventions. There is a need for timely submission of data. We recommend that the National Buruli Ulcer Control Program (NBUCP) provides logistical support to treatment centres.